Prevalence and risk factors for postnatal mental health problems in mothers of infants admitted to neonatal care: Analysis of two population-based surveys in England - Gong,J; Fellmeth,G; Quigley,MA; Gale,C; Stein,A; Alderdice,F; Harrison,S (BMC Pregnancy and Childbirth, 2023)
BackgroundPrevious research suggests that mothers whose infants are admitted to neonatal units (NNU) experience higher rates of mental health problems compared to the general perinatal population. This study examined the prevalence and factors associated with postnatal depression, anxiety, post-traumatic stress (PTS), and comorbidity of these mental health problems for mothers of infants admitted to NNU, six months after childbirth.MethodsThis was a secondary analysis of two cross-sectional, population-based National Maternity Surveys in England in 2018 and 2020. Postnatal depression, anxiety, and PTS were assessed using standardised measures. Associations between sociodemographic, pregnancy- and birth-related factors and postnatal depression, anxiety, PTS, and comorbidity of these mental health problems were explored using modified Poisson regression and multinomial logistic regression.ResultsEight thousand five hundred thirty-nine women were included in the analysis, of whom 935 were mothers of infants admitted to NNU. Prevalence of postnatal mental health problems among mothers of infants admitted to NNU was 23.7% (95%CI: 20.6–27.2) for depression, 16.0% (95%CI: 13.4–19.0) for anxiety, 14.6% (95%CI: 12.2–17.5) for PTS, 8.2% (95%CI: 6.5–10.3) for two comorbid mental health problems, and 7.5% (95%CI: 5.7–10.0) for three comorbid mental health problems six months after giving birth. These rates were consistently higher compared to mothers whose infants were not admitted to NNU (19.3% (95%CI: 18.3–20.4) for depression, 14.0% (95%CI: 13.1–15.0) for anxiety, 10.3% (95%CI: 9.5–11.1) for PTS, 8.5% (95%CI: 7.8–9.3) for two comorbid mental health problems, and 4.2% (95%CI: 3.6–4.8) for three comorbid mental health problems six months after giving birth. Among mothers of infants admitted to NNU (N = 935), the strongest risk factors for mental health problems were having a long-term mental health probl